Anhydroicaritin Inhibits EMT in Breast Cancer by Enhancing GPX1 Expression: A Research Based on Sequencing Technologies and Bioinformatics Analysis - Li, Feifei; Shi, Youyang; Yang, Xiaojuan; Luo, Zhanyang; Zhang, Guangtao; Yu, Kui; Li, Feng; Chen, Lixin; Zhao, Youkang; Xie, Ying; Wu, Yuanyuan; Yang, Jianfeng; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background: Breast cancer (BC) is the main cause of cancer-related deaths in women worldwide. The application of advanced technology has promoted accurate diagnosis and treatment of cancer. Anhydroicaritin (AHI) is a flavonoid with therapeutic potential in BC. This study aimed to determine the mechanism of AHI in the treatment of BC via RNA sequencing, comprehensive bioinformatics analysis, combined with experimental verification.Methods: Network pharmacology and MTT experiments were used to preliminarily confirm the anti-BC effect of AHI. RNA sequencing was used to find the genes that AHI affected. Differential expression, survival analysis, gene set enrichment analysis (GSEA), and immune infiltration analysis were performed through bioinformatics analysis. Western blotting, RT-PCR, molecular docking and DARTS experiments were used to confirm the direct effect of AHI on GPX1. Finally, BC nude mouse xenografts were established and the molecular mechanism of AHI on BC were explored. Results: Network pharmacology results showed that therapeutic targets of AHI on BC was related to the proliferation, invasion and metastasis. AHI significantly inhibited the proliferation of 4T1 and MDA-MB-231 BC cells. RNA sequencing results showed that AHI up-regulated the expression of GPX1 both in 4T1 and MDA-MB-231 BC cells. GPX1 is less expressed in BC than normal breast tissues. There was a tendency that patients with GPX1 high expression had longer overall survival and disease-free survival than patients with GPX1 low expression in BC. AHI increased the protein and mRNA levels of GPX1. Molecular docking and DARTS confirmed the direct combination between AHI and GPX1. After EMT score was evaluated in 1,078 patients with BC, we found potential anti-BC role of GPX1 possibly via suppression of malignant epithelial-mesenchymal transition (EMT) process. Animal experiments showed AHI had a significant inhibitory effect on the growth of tumors. Moreover, AHI inhibited EMT by enhancing GPX1 and cleaved-caspase3, inhibiting EMT marker (N-cadherin and Vimentin) and Ki-67. Conclusion: GPX1 plays a critical role in BC, which might be a biomarker for the prognosis. Additionally, AHI suppressed EMT by increasing the expression of GPX1, which may serve as a potential therapy for the treatment of BC.